Chloroform exposure and risk of leukemia: systematic review and meta-analysis - Soleimani, Yaser; Mahmoudi, Sheyda; Daraei, Mahdi; Aryanejad, Ali; Sani, Ali Hosseini; Khazali, Alireza; Khorsand, Soroush; Mahdavi, Mohammadreza; Sabeti, Setareh; Sadeghi, Hamid; Shahsavari, Mohammad Javad; Varseh, Mahdieh; et al. (Frontiers in Public Health, 2025)
ObjectivesThe aim of this systematic review and meta-analysis was to evaluate the association between chloroform exposure and the risk of leukemia, quantify the overall risk, and identify potential sources of heterogeneity among different leukemia subtypes.MethodsA comprehensive literature search was conducted across PubMed, Web of Science, and Scopus to identify relevant epidemiological studies published up to December 2023. Inclusion criteria focused on human studies that assessed chloroform exposure and reported leukemia incidence or mortality. Data were extracted and analyzed using random-effects models to calculate pooled odds ratios (ORs) with 95% confidence intervals (CIs). Heterogeneity was assessed using I2, τ2, and Cochran’s Q test. Publication bias was evaluated using Begg’s test.ResultsFour case–control studies were included, spanning publication years from 2001 to 2023, with sample sizes ranging from 67 to 31,292 participants. The overall pooled OR for the association between chloroform exposure and leukemia was 0.75 (95% CI: 0.25–2.27), indicating no statistically significant association. However, substantial heterogeneity was observed (I2 = 95%). Begg’s test showed no significant publication bias (p = 1.0000).ConclusionThis systematic review and meta-analysis did not find a significant overall association between chloroform exposure and leukemia risk. The significant association observed for AML suggests that chloroform exposure might increase the risk of this specific subtype, while the reduced risk for CLL warrants further investigation. The high heterogeneity underscores the need for standardized methodologies and further research to clarify these associations, particularly focusing on different leukemia subtypes, exposure levels, and population characteristics. These findings can inform public health policies and targeted prevention strategies to mitigate potential risks associated with chloroform exposure.Clinical trial registration/systematic review registrationhttps://www.waocp.com/journal/index.php/apjec/article/view/1283.